Influence of aphotic haloclines and euxinia on organic biomarkers and microbial communities in a thalassohaline and alkaline volcanic crater lake. Issue 2 (23rd October 2021) - Sala, David; Grossi, Vincent; Agogué, Hélène; Leboulanger, Christophe; Jézéquel, Didier; Sarazin, Gérard; Antheaume, Ingrid; Bernard, Cécile; Ader, Magali; Hugoni, Mylène
Abstract: Studies on microbial communities, and their associated organic biomarkers, that are found thriving in the aphotic euxinic waters in modern stratified ecosystems are scarce compared to those undertaken in euxinic photic zones. The Dziani Dzaha (Mayotte, Indian Ocean) is a tropical, saline, alkaline crater lake that has recently been presented as a modern analog of Proterozoic Oceans due to its thalassohaline classification (having water of marine origin) and specific biogeochemical characteristics. Continuous intense photosynthetic production and microbial mineralization keep most of the water column permanently aphotic and anoxic preventing the development of a euxinic (sulfidic and anoxic) photic zone despite a high sulfide/sulfate ratio and the presence of permanent or seasonal haloclines. In this study, the molecular composition of the organic matter in Lake Dziani Dzaha was investigated and compared to the microbial diversity evaluated through 16S rRNA gene amplicon sequencing, over two contrasting seasons (rainy vs. dry) that influence water column stratification. Depth profiles of organic biomarker concentrations (chlorophyll‐a and lipid biomarkers) and bacterial and archaeal OTU abundances appeared to be strongly dependent on the presence of aphotic haloclines and euxinia. OTU abundances revealed the importance of specific haloalkaliphilic bacterial and archaeal assemblages in phytoplanktonic biomass recycling and the biogeochemical functioning of the lake, suggesting new haloalkaline non‐phototrophic anaerobic microbial precursors for some of the lipid biomarkers. Uncultured Firmicutes from the family Syntrophomonadaceae (Clostridiales), and Bacteroidetes from the ML635J‐40 aquatic group, emerged as abundant chemotrophic bacterial members in the anoxic or euxinic waters and were probably responsible for the production of short‐chain n ‐alkenes, wax esters, diplopterol, and tetrahymanol. Halocline‐dependent euxinia also had a strong impact on the archaeal community which was dominated by Woesearchaeota in the sulfide‐free waters. In the euxinic waters, methanogenic Euryarchaeota from the Methanomicrobia, Thermoplasmata, and WSA2 classes dominated and were likely at the origin of common hydrocarbon biomarkers of methanogens (phytane, pentamethyl‐eicosenes, and partially hydrogenated squalene).